An approach towards modification of UiO-type MOFs with phosphonate-substituted porphyrins. (1st June 2022) - Birin, Kirill P.; Shlykov, Ivan V.; Senchikhin, Ivan N.; Demina, Liudmila I.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu
Graphical abstract: The post-modification of UiO-66 with a porphyrin bearing phosphonic acid moieties is reported. The preservation of thermal stability and crystallinity of the material is revealed. The binding motif is investigated by FT-IR and UV–vis. The specific surface area of the material is decreased in comparison with the starting UiO-66, proving the surface localization of the porphyrin. Abstract: The post-modification of UiO-type materials with a porphyrin bearing phosphonic acid moieties is reported for the first time. The prolonged interaction of UiO-66 and tetrakis(4-phosphonatophenyl)porphyrinato nickel(II) Ni (H 8 -TPPP ) resulted in the formation of a hybrid material with the preservation of the crystallinity of the material. The measured specific surface area of Ni (H 8 -TPPP@UiO-66 ) showed considerable decrease of the corresponding value in comparison with the starting UiO-66 (from 1181 to 619 m 2 /g), providing indirect proof of the localization of the porphyrin at the surface of the material crystallites. The prepared hybrid material was excessively characterized with a set of physical–chemical methods. The preservation of the thermal stability up to 400 °C is revealed, moreover the thermogravimetric data allowed to evaluate the ratio of the grafted porphyrin as ca . 18% by weight. UV–vis reflectance data of the hybrid material were found to be in consistency with the spectra of the starting porphyrin allowing to assume the absence of its intermolecular interactions at the surface of UiO. The analysis of the FT-IR spectra of the obtained material and its precursors allowed assuming the binding motifs of the phosphonic acid residues.